Métodos efectivos para la evaluación de la lateralidad en los niños de inicial 2 de la Unidad Educativa Vicente Anda Aguirre del cantón Mocha. - Miniguano Calero, Geomaira Stefania (2025)
The main objective of this research is to determine the effective method to help the evaluation of laterality in children in early childhood education 2, therefore laterality is conceptualized as the motor predominance of one side of the body over the other, affecting mainly the hand, foot, sight and hearing, it is necessary to act immediately because it affects spatial orientation and academic performance. On the other hand. educational evaluation is a crucial process that seeks to analyze the performance and learning of students where information is collected through various tools to identify strengths and weaknesses that allow teachers to create teaching strategies that ensure a comprehensive development. This study is focused on effective methods to evaluate laterality for which a mixed methodology was used that combines quantitative and qualitative elements through the use of bibliographic sources, the research design is non- experimental because it uses techniques used through observation in this case the instrument used was the observation sheet with a population of 15 children of initial 2, obtaining as results of this research that laterality is fundamental in the development of children to develop it different methods should be used because each child is different.